Exposure profiles, seasonal variation and health risk assessment of BTEX in indoor air of homes at different microenvironments of a terai province of northern India. (June 2017) - Masih, Amit; Lall, Anurag S.; Taneja, Ajay; Singhvi, Raj
Abstract: BTEX are known for their ability to deteriorate human health. A monitoring study was conducted at Gorakhpur, for a span of one year. BTEX were sampled by drawing air through activated charcoal tubes, using a low flow SKC model 220 pump. Samples were extracted with CS2 followed by subjecting the aromatic fraction to GC-FID. The mean concentration of BTEX was highest at agricultural (54.3 μg m −3 ) followed by industrial (18.2 μg m −3 ), roadside (12.3 μg m −3 ) and residential site (6.1 μg m −3 ). Toluene levels were higher than benzene at all the sites except agricultural site, where benzene concentration exceeded toluene. Seasonal variation showed highest BTEX concentration during winters (32.56 μg m −3 ) followed by monsoon (19.90 μg m −3 ) and summers (14.44 μg m −3 ). At each site, BTEX levels increased with decrease in temperature. Benzene and toluene levels were plotted against indoor temperature, which revealed a significant linear correlation (p < 0.001) for each plot. BTEX concentrations were compared between different sites using Student's t and Mann Whitney U tests. Value of integrated lifetime cancer risk (ILTCR) was higher than 10 −6 for benzene at all the sites, while for ethylbenzene, it was only higher at agricultural site. Cumulative hazard index (HI) was lower than 1.0 at all the sites. Highlights: The indoor concentrations of BTEX were measured at four locations in the city of Gorakhpur. The samples were extracted CS2 and the aromatic fraction was subjected to GC-FID. Average BTEX were found to be highest at agricultural site during winters. Integrated lifetime cancer risk value was higher than 10 −6 for benzene at all the sites, while for ethylbenzene, it was only higher at agricultural site. Cumulative Hazard Index was lower than 1.0 at all the sites.